The common parasite Toxoplasma gondii induces prostatic inflammation and microglandular hyperplasia in a mouse model. Issue 10 (12th May 2017) - Colinot, Darrelle L.; Garbuz, Tamila; Bosland, Maarten C.; Wang, Liang; Rice, Susan E.; Sullivan, William J.; Arrizabalaga, Gustavo; Jerde, Travis J.
Abstract : Background: Inflammation is the most prevalent and widespread histological finding in the human prostate, and associates with the development and progression of benign prostatic hyperplasia and prostate cancer. Several factors have been hypothesized to cause inflammation, yet the role each may play in the etiology of prostatic inflammation remains unclear. This study examined the possibility that the common protozoan parasite Toxoplasma gondii induces prostatic inflammation and reactive hyperplasia in a mouse model. Methods: Male mice were infected systemically with T. gondii parasites and prostatic inflammation was scored based on severity and focality of infiltrating leukocytes and epithelial hyperplasia. We characterized inflammatory cells with flow cytometry and the resulting epithelial proliferation with bromodeoxyuridine (BrdU) incorporation. Results: We found that T. gondii infects the mouse prostate within the first 14 days of infection and can establish parasite cysts that persist for at least 60 days. T. gondii infection induces a substantial and chronic inflammatory reaction in the mouse prostate characterized by monocytic and lymphocytic inflammatory infiltrate. T. gondii ‐induced inflammation results in reactive hyperplasia, involving basal and luminal epithelial proliferation, and the exhibition of proliferative inflammatory microglandular hyperplasia in inflamed mouse prostates. Conclusions: This study identifies the common parasite T. gondii as a new trigger of prostatic inflammation, which we used to develop a novel mouse model of prostatic inflammation. This is the first report that T. gondii chronically encysts and induces chronic inflammation within the prostate of any species. Furthermore, T. gondii ‐induced prostatic inflammation persists and progresses without genetic manipulation in mice, offering a powerful new mouse model for the study of chronic prostatic inflammation and microglandular hyperplasia.